تقييم واقع الفحوم الهيدروجينية الاليفاتية الـ (AHCs) في الرسوبيات السطحية الشاطئية لمدينة طرطوس (Latakia University Journal -Basic Sciences Series, 2018)
جمعت عينات رسوبية شاطئية من الرسوبيات البحرية من سبعة مواقع ممتدة على طول شاطئ مدينة طرطوس وذلك خلال الفترة الممتدة من 1/6/2001 وحتى 15/6/2002 . وجرى استخلاصها ودراستها كميا ونوعياً باستخدام تقانة الكروموتوغرافيا الغازية المزودة بكاشف التشرد باللهب GC-FID من اجل تعيين الفحوم الهيدروجينية الاليفاتية (AHCs). سجلـت تراكيز الـ (AHCs) في الرسوبيات المدروسة في المجال52.05- 582.01 ng/g (dry wt. ). كانت أعلى التراكيز في المحـطتين st3 و st2 وأخفضها في المحطات st4 و  st5و st1.ترتبط تراكيز الـ  (AHCs)في المناطق المدروسة بعوامل عدة أهمها وجود روافد خارجية تحمل معها مياه الصرف الصحي واردة من المنشآت الصناعية والخدمية والتجمعات السكانية لتصب في مياه البحر، بالإضافة إلى وجود نشاط بشري كثيف وخاصة في  مرفأ قوارب النقل إلى جزيرة أرواد والصيد البحري. Samples of superficial sediments have been collected from seven sites of Tartous city coast during the period (1/6/2001-15/6/2002). The samples have extracted to determine the qualitative and quantitive content of Aliphatic Hydrocarbons (AHCs), using the GC-FID technique. The concentration of (AHCs) ranges between 52.05 and 582.01 ng/g (dry wt.). The highest concentration has been reported in st3 and st2,while the lowest concentration has been reported in st4 , st5 and st1. This study demonstrates that the concentrations of (AHCs) reported in the studied sites are related to a variety of factors. The most important factor is the presence of external tributaries carrying    sewage of some factories and residential areas , which is then discharged into the sea. In addition,  the extensive human activity, particularly in Arwad Isle  and in the fishing  harbor is also a crucial factor in increasing the concentration of (AHCs).